Mutated GM‐CSF‐based CAR‐T cells targeting CD116/CD131 complexes exhibit enhanced anti‐tumor effects against acute myeloid leukaemia. Issue 5 (6th May 2021) - Hasegawa, Aiko; Saito, Shoji; Narimatsu, Shogo; Nakano, Shigeru; Nagai, Mika; Ohnota, Hideki; Inada, Yoichi; Morokawa, Hirokazu; Nakashima, Ikumi; Morita, Daisuke; Ide, Yuichiro; Matsuda, Kazuyuki; et al.
Abstract: Objectives: As the prognosis of relapsed/refractory (R/R) acute myeloid leukaemia (AML) remains poor, novel treatment strategies are urgently needed. Clinical trials have shown that chimeric antigen receptor (CAR)‐T cells for AML are more challenging than those targeting CD19 in B‐cell malignancies. We recently developed piggyBac ‐modified ligand‐based CAR‐T cells that target CD116/CD131 complexes, also known as the GM‐CSF receptor (GMR), for the treatment of juvenile myelomonocytic leukaemia. This study therefore aimed to develop a novel therapeutic method for R/R AML using GMR CAR‐T cells. Methods: To further improve the efficacy of the original GMR CAR‐T cells, we have developed novel GMR CAR vectors incorporating a mutated GM‐CSF for the antigen‐binding domain and G4S spacer. All GMR CAR‐T cells were generated using a piggyBac ‐based gene transfer system. The anti‐tumor effect of GMR CAR‐T cells was tested in mouse AML xenograft models. Results: Nearly 80% of the AML cells predominant in myelomonocytic leukaemia were found to express CD116. GMR CAR‐T cells exhibited potent cytotoxic activities against CD116 + AML cells in vitro . Furthermore, GMR CAR‐T cells incorporating a G4S spacer significantly improved long‐term in vitro and in vivo anti‐tumor effects. By employing a mutated GM‐CSF at residue 21 (E21K), the anti‐tumor effects of GMR CAR‐T cells were also improved especially in long‐term in vitro settings. Although GMR CAR‐T cells exerted cytotoxic effects on normal monocytes, their lethality on normal neutrophils, T cells, B cells and NK cells was minimal. Conclusions: GMR CAR‐T cell therapy represents a promising strategy for CD116 + R/R AML. Abstract : This study introduces a new CAR‐T therapy for acute myeloid leukaemia (AML) that targets the GM‐CSF receptor complex. GM‐CSF receptors are a novel target for AML treatment in the CAR‐T field. Furthermore, by modifying the spacer (G4S) and employing a mutated GM‐CSF construct (E21K), we could remarkably improve the anti‐tumor effects of CAR‐T cells in multiple mouse xenograft models.